Situational Perception Correlation Study, Situational Motivation, and Communication Actions in Malang Brawijaya University Students on the Issue of Sexual Harassment in Indonesian Higher Education Environment in 2022 - Al Gazali, M. Ahmi Al Gazali; Kriyantono, Rachmat; Wulandari, Maulina Pia (Technium Social Sciences Journal, 2023)
This study tests the theoretical model of Kim and Grunig's situational theory of problem solving (STOPS) (2011), in explaining how the correlation of situational perceptions, situational motivation, and communication actions in students of Brawijaya University Malang in 2022 from the issue of sexual harassment in Indonesian tertiary institutions. Survey of 425 students in August-September 2022 in 15 faculties. Based on the results of path analysis from the SmartPLS 3.0 structural equation modeling procedure, this study confirms the correlation of the main propositions of the STOPS theory, namely situational perceptions, situational motivations, and communication actions on the issue of sexual harassment in Indonesian tertiary institutions.